The Friction Coefficient Investigation during Electrochemical Baromembrane Separation of Model Solutions - Shestakov, K.V. (Journal of Applied Solution Chemistry and Modeling, 2022)
A large number of scientific papers in recent decades have been devoted to the mathematical description of a mass transfer of substances through membranes. The choice of a mathematical model is to be carried out depending on the specific separation process used. This study represents a verification of how the predicted value of the solute flow density obtained using pre-calculated friction coefficients corresponds to real experimental data for electrochemical baromembrane separation of model solutions. The experimental and theoretically calculated values of the Ni (II), Cu (II), and Fe (III) cations flux density through the heterogeneous cellulose acetate membranes MGA-95 and MGA-100 are compared. It is established that the use of the mass transfer friction model is quite effective in predicting the kinetic characteristics of electrochemical membrane separation of solutions using semipermeable membranes. The calculation error in most cases is within one percent.